TREATMENT OF HYPERTENSION IN PREGNANCY: GUIDELINES AND CLINICAL EXPERIENCE - O. V. Gaisenok; O. A. Zamyatina; N. Yu. Denisova; A. S. Leonov (Рациональная фармакотерапия в кардиологии, 2015)
Topical issues of the treatment of hypertension in pregnancy are presented. Examples from clinical practice are discussed as well as possible medical treatment of hypertension in pregnant women taking into account actual recommendations.